Taram Rural Tourism Development Post Covid-19 Pandemic - Iis Ismawati; Nurul Fauzi; Ranti Komala Dewi; Andrik Marta; Ermiati (International ABEC, 2022)
The Covid-19 pandemic has caused an enormous impact on the tourism industry not only at the global level but also at the local level. The result of this pandemic turned out to be worse than the effects of previous crises such as the SARS pandemic in 2003 and the shock of the 2009 economic crisis. Presently the tourism sector is trying to recover and revive from adversity. Several studies show that successful companies and communities in the pandemic era are those who can transform into the mega-shifts of the new tourism industry landscape. Characterized by four characteristics namely Hygiene, Low-Touch, Less-Crowd, and Low Mobility Based on these characteristics, the rural tourism industry is a kind of tourism that is considered suitable for it. Because in general, rural areas have many natural tourist destinations. Where natural tourism has become a trend for post-Covid-19 pandemic tourist destinations. The sudden pandemic Covid-19 has fostered new habits, making health and safety a top priority for visitors. Nature tourism is a popular trend that is favored by the public in new normal conditions. In the future, the types of destinations and attractions that offer the concept of nature, eco, wellness, and adventure (NEWA) will be more in demand and become the new mainstream in the tourism industry. In the future, NEWA's innovations will evolve rapidly to capture this shift in traveler preferences. This Assistance's purpose to explore the potential of rural Taram in developing the tourism sector which had slumped due to the impact of the Covid-19 pandemic. Tourism is a strategic sector for rural Taram because it can become the largest contributor to Original Local Government Revenue. Assistance implementation methods include potential surveys, Focus Group Discussions, and mentoring. The results confirm that the village of Taram has potential assets in the form of a diversity of natural resources, especially forestry and agriculture, the strength of human resources that are open to change, economic assets, social capital, physical assets, and historical, cultural, and spiritual assets. Local government should determine priority potential assets to be developed as tourist destinations. Natural and cultural tourism based on local potential has the opportunity to be further developed in the future. The Development of rural tourism could enable destinations to manage unpredictable crises, apply the sustainable tourism and resilience concepts